BUGUNGI KUN YOSHLARI O‘RTASIDA SOG‘LOM TURMUSH TARZINI SHAKLLANTIRISH MASALALARI.: BUGUNGI KUN YOSHLARI O‘RTASIDA SOG‘LOM TURMUSH TARZINI SHAKLLANTIRISH MASALALARI. - Raxmonqulova, Xolida (Maktabgacha taʼlim jurnali, 2021)
In the article on the balance of healthy living of young people solving the problem of circulation. At the same time the family, the neighborhood their educators solve the problem.